2022
DOI: 10.3390/molecules27175434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Anticancer Efficacy Studies of Iridium (III) Polypyridyl Complexes against Colon Cancer HCT116 Cells

Abstract: In this paper, two new iridium (III) complexes, [Ir(ppy)2(ipbp)](PF6) (Ir1) (ppy = 2-phenylpyridine, ipbp = 3-(1H-imidazo[4,5-f][1,10]phenanthrolin-2yl)-4H-chromen-4-one) and [Ir(bzq)2(ipbp)](PF6) (Ir2) (bzq = benzo[h]quinolone), were synthesized and characterized. The cytotoxicity of the complexes against human colon cancer HCT116 and normal LO2 cells was evaluated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. The complexes Ir1 and Ir2 show high cytotoxic efficacy toward HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…To understand in which phase the anticancer agents arrest the cancer cell cycle, it is very important to carry out the cell cycle analysis [28]. For present study, the propidium iodide stained CAL27 cells (after treatment with NQA-1 with IC50 of 13.2 µg/mL) revealed that cell content percentage in the G0/ G1, G2M and S phase was 16.86%, 9.64% and 73.5%.…”
Section: Resultsmentioning
confidence: 84%
“…To understand in which phase the anticancer agents arrest the cancer cell cycle, it is very important to carry out the cell cycle analysis [28]. For present study, the propidium iodide stained CAL27 cells (after treatment with NQA-1 with IC50 of 13.2 µg/mL) revealed that cell content percentage in the G0/ G1, G2M and S phase was 16.86%, 9.64% and 73.5%.…”
Section: Resultsmentioning
confidence: 84%
“…Malignant cells' capacity to avoid apoptosis is a dening characteristic of cancer. 53,54 Upcoming innovative anticancer agents could show their efficacy by inducing the apoptotic process through stimulation of proapoptotic molecules and inhibition of anti-apoptotic molecules. Using propidium iodide (PI) and annexin-V-FITC, ow cytometry was performed to assess the induction of apoptosis in HCT-116 cells.…”
Section: Chemistrymentioning
confidence: 99%